2018
DOI: 10.21037/jtd.2018.05.202
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pulmonary rehabilitation and correlations in between functional parameters, extent of thoracic surgery and severity of post-operative complications: randomized clinical trial

Abstract: Pulmonary rehabilitation can reduce the functional depletion caused by the thoracic surgical operation. Identification of more predictive factors of severe complications can help making preoperative risk stratification more precisely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 20 publications
0
55
1
3
Order By: Relevance
“…Smoking has a huge impact on cardiopulmonary diseases and cancer (14). Based on our experience, the quitting rate can be much higher (70-75%) in perioperative condition (5,6).…”
Section: Smokingmentioning
confidence: 89%
See 2 more Smart Citations
“…Smoking has a huge impact on cardiopulmonary diseases and cancer (14). Based on our experience, the quitting rate can be much higher (70-75%) in perioperative condition (5,6).…”
Section: Smokingmentioning
confidence: 89%
“…We need to focus on functional and quality of life variables, which may help maximize surgery safety and improve the post-surgical period (3). There is still a debate in the preoperative risk stratification in thoracic surgery, including esophagectomy (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the definition by the American Thoracic Society and the European Respiratory Society, PR refers to “a comprehensive intervention based on a thorough assessment of the patient followed by individualized treatment, including but not limited to exercise training, education, and behavior change, aimed at improving the physical and mental status of patients with CRDs and at promoting long-term adherence to health-enhancing behaviors” ( 17 ). Since the introduction of PR programs, reassuring results have been achieved in the treatment of CRDs, and health care providers have gradually realized that PR constitutes a pivotal basic measure in managing individuals with COPD ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are only few studies discussing the parameters affecting surgical complications. Attila Vagvolgyi et al 3 discussed that kilometers travelled via cycle ergometer at the onset of the preoperative rehabilitation, gender, forced expiratory volume in 1 s (FEV 1 ) after preoperative rehabilitation, extent of the operation and 6-minute walk test (6MWT) before preoperative rehabilitation could predict severe complications correctly in 72.5% of the patients with COPD who underwent thoracic surgery. Yutian LAI et al 4 demonstrated that preoperative COPD and WBC count were independent risk factors for postoperative cardio-pulmonary complications in the patients who underwent lobectomy for stage I non-small cell lung cancer.…”
Section: Introductionmentioning
confidence: 99%